2022
DOI: 10.1186/s40168-022-01353-5
|View full text |Cite
|
Sign up to set email alerts
|

Selected commensals educate the intestinal vascular and immune system for immunocompetence

Abstract: Background The intestinal microbiota fundamentally guides the development of a normal intestinal physiology, the education, and functioning of the mucosal immune system. The Citrobacter rodentium-carrier model in germ-free (GF) mice is suitable to study the influence of selected microbes on an otherwise blunted immune response in the absence of intestinal commensals. Results Here, we describe that colonization of adult carrier mice with 14 selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…In addition to the LD regimen itself, antibiotic treatment as prophylactic intervention does cause dysbiotic states. Experimental approaches have shown that the microbial composition and commensalderived metabolites crucially impact on host immunity, thereby shaping either tolerogenic or activating environments (88,89). Further, recent studies have shown that the microbiome is capable of influencing the functionality of CD19-specific CAR-T cells in patients.…”
Section: Influence On the Microenvironmentmentioning
confidence: 99%
“…In addition to the LD regimen itself, antibiotic treatment as prophylactic intervention does cause dysbiotic states. Experimental approaches have shown that the microbial composition and commensalderived metabolites crucially impact on host immunity, thereby shaping either tolerogenic or activating environments (88,89). Further, recent studies have shown that the microbiome is capable of influencing the functionality of CD19-specific CAR-T cells in patients.…”
Section: Influence On the Microenvironmentmentioning
confidence: 99%
“…Experimentation with germ-free mouse models demonstrated that this arrested angiogenic program is rapidly restarted by colonization with a gut microbiota or the abundant polysaccharide-degrading, Gram-negative bacterium Bacteroides thetaiotaomicron (Stappenbeck et al 2002). Furthermore, the minimal microbial consortium oligo-mouse microbiota (OMM 12 ), a community of 12 mouse intestinal bacteria, was demonstrated to enhance the maturation of small intestinal villus capillaries (Garzetti et al 2017;Romero et al 2022).…”
Section: Microbiota-host Interactions Affect the Gut Microvasculaturementioning
confidence: 99%
“… 47 , 48 Gut microbiota has various physiological functions in the host, including strengthening epithelial-intestinal barrier integrity, 49 maintenance of energy homeostasis, 50 protection against pathogens, 51 and regulation of host immunity. 52 …”
mentioning
confidence: 99%